Comparison of Health Service Policies in Indonesia and Malaysia: A Literature Review Approach - Kurniawan, Yanuar; Suharto, Didik Gunawan; Setyowati, Kristina (Technium Social Sciences Journal, 2025)
This study aims to compare health care policies in Indonesia and Malaysia based on literature analysis. Using a literature review method, this article explores the implementation of the Contribution Assistance Program (PBI) in Indonesia, as well as national health care quality policies in Malaysia. The study finds that both countries have different approaches in addressing the challenges of accessibility and quality of health care, with Malaysia emphasizing more on an integrated national quality strategy, while Indonesia focuses on equal access through subsidy programs. This study offers insights into opportunities for policy improvement in both countries to support more inclusive and sustainable health systems.